CRIMINOLOGY MODEL OF CRIME PREVENTION IN THE FAMILY SPHERE - Bogatyrov, Ivan; Buriak, Kateryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: scientific and methodological understanding of the development and introduction of a criminological model of crime prevention in the family sphere into domestic criminological science. Research methods: logical-legal, formal-legal, cognitive-analytical, comparative-legal analysis, deduction and others. Results: the author’s definition of the criminological model of crime prevention in the family sphere was formulated. A road map of the criminological model is proposed. Discussion: the criminalization of crime in the family sphere, which took place in connection with changes in the 21st century in socio-economic and political processes, which required at the same time criminal-legal protection of the legal rights and interests of a person and a citizen in various spheres of his/her life, including and in the family sphere. It is proved that the specified model is based on our definition of a real goal; cover a wide range of subjects (state and non-state structures). It is worth noting that crime in the family sphere is not an accidental fact of human destructiveness, it is a high level of quantitative and qualitative indicators of criminal offenses committed by an offender in the family sphere. Since this crime has a tendency to increase, we have set the task of actualizing a comprehensive study of all interrelated aspects, on the basis of which a criminological model and effective mechanisms of its counteraction and prevention can be developed. Since the prevention of crime in the family sphere as an object of criminological modeling was not the subject of a separate study, we decided in this article to develop a road map for such modeling and to propose the scientific community to start a discussion on finding ways to prevent crime in the family sphere. The opinion that many victims perceive crime in the family sphere as an inevitable phenomenon in life, and do not report it is well-founded. Other victims who have the courage to seek help from the authorities are sometimes sent back without being taken seriously. Others cannot find protection and justice because of the weakness of the legal framework. It is the family safety of the family that should become the impetus that will form zero tolerance for such a crime and show that every person has the right to be treated with dignity and protection. As for the objects of crime prevention in the family sphere, they include various processes and phenomena. These are economic, political, psychological and other factors that determine the level and dynamics of crime in the family sphere. The degree of connection of these factors with crime can be different. Knowing it with the help of criminological analysis determines the scope of preventive activities and its effectiveness.